Impact of sludge retention time on MBR fouling: role of extracellular polymeric substances determined through membrane autopsy. Issue 7 (9th August 2017) - Silva, Ana F.; Antunes, Silvia; Freitas, Filomena; Carvalho, Gilda; Reis, Maria A. M.; Barreto Crespo, Maria T.
Abstract: The impact of sludge retention time (SRT) on the biofouling of a membrane bioreactor (MBR) by extracellular polymeric substances (EPS) was investigated. The MBR was operated at 60 and 20 d SRT. The gel layer (recovered through optimized membrane autopsy methods) and the cake layer were analyzed for their content and profile of EPS proteins and polysaccharides. The change to a shorter SRT led to decreased membrane filterability, concomitant with a higher expression of EPS proteins in the cake layer, which were identified as being mainly related with biosynthesis and stress functions. The gel layer was more substantial in internal fibers, with polysaccharides being the major component in this layer. With the decrease in SRT (and filterability decrease), the overall polysaccharide content and sugar variety increased. In conclusion, SRT impacted not only on the quantity but also the composition of EPS molecules, and both were shown to be important in biofouling.